2002
DOI: 10.1007/s00216-002-1247-5
|View full text |Cite
|
Sign up to set email alerts
|

Air monitoring of aldehydes by use of hydrazine reagents with a triazine backbone

Abstract: Two hydrazine reagents, 4- N, N-dimethylamino-6-(4'-methoxy-1'-naphthyl)-1,3,5-triazine-2-hydrazine (DMNTH) and N-methyl-4- N', N'-dimethylamino-6-(4'-methoxy-1'-naphthyl)-1,3,5-triazine-2-hydrazine (MDMNTH) have been synthesized and used for the determination of aldehydes in air samples. Test tubes with the reagents coated on silica gel were prepared and used for monitoring of carbonyls in air. After elution with acetonitrile the hydrazones formed were separated by reversed-phase liquid chromatography. Detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Low limits of detection and high derivatization yields [13] ( Table 3). Electrochromatography offers the advantages of high separation efficiency to deal with liquid samples similar to HPLC [18].…”
Section: Background For Carbonyl Analysismentioning
confidence: 98%
See 2 more Smart Citations
“…Low limits of detection and high derivatization yields [13] ( Table 3). Electrochromatography offers the advantages of high separation efficiency to deal with liquid samples similar to HPLC [18].…”
Section: Background For Carbonyl Analysismentioning
confidence: 98%
“…Humidity can be a serious problem for carbonyl measurement by the HPLC method [13,37]. Ferrari et al [4] reported that saturated aliphatic (or aromatic aldehyde) hydrazones are not affected by water, whilst acetone hydrazone is strongly hydrolyzed in the presence of up to 10% water (in trapping acetonitrile solution in the impinger technique).…”
Section: Choice Of Hydrazinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Test tubes coated with DMNTH have been used for the determination of aldehydes in air samples followed by chromatographic separation and detection by UV-Vis and fluorescence spectroscopy, the results were found to be comparable to the established method using the derivatization reagent DNPH [13]. The most recent application of DMNTH reported [9], is for the derivatization and analysis of a range of carbonyl containing compounds by laser desorption ionisation-mass spectrometry (LDI-MS).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a number of methods employed to assay pesticides using different detectors as fluorimetric, [11][12][13][14][15][16][17] photometric [18][19][20] and electrochemical, [21][22][23] some problems still arise associated with the complexity of the matrices, particularly in the case of HS solutions where the ionic strength is so high that the common methods frequently fail. To overcome this difficulty, large dilution factors are often used but with prejudice to the sensitivity of the methods.…”
Section: Introductionmentioning
confidence: 99%